Silica aerogel/polyester blankets for efficient sound absorption in buildings. (30th September 2019) - Talebi, Zahra; Soltani, Parham; Habibi, Negar; Latifi, Fatemeh
Graphical abstract: Highlights: Lightweight sound absorbers with long service life were produced. Silica aerogel/PET blankets enjoy higher SAC than their untreated counterparts. SAC is strongly affected by the pore structure and density of aerogel particles. Hydrophobic aerogels/PET blanket for sound absorption applications were produced. Hydrophobic aerogel blankets show higher SAC as compared with hydrophilic blankets. Abstract: In this paper sound absorption characteristics of silica aerogel/polyester (PET) blankets are investigated. PET fibers were made on an industrial scale compact melt spinning line and then processed on a laboratory scale needling line to produce nonwoven fabrics. The silica aerogel blankets were prepared by in situ synthesis of silica aerogel on the nonwoven fabrics via a two-step sol-gel process of tetraethoxysilane which was followed by drying at ambient pressure. In order to achieve aerogel particles with different pore structure and properties, various synthesis conditions were used. The nonwoven samples were characterized in terms of thickness, fiber diameter, porosity and pore size by X-ray micro-computed tomography and scanning electron microscopy. Moreover, nitrogen adsorption analysis was carried out to determine the specific surface area and pore structure of aerogel particles. The effect of pore structure, physical properties and hydrophobicity of aerogel particles on sound absorption coefficient (SAC) of blankets was investigated using two-microphone transfer function method. Also, the effect of sol volume and nonwoven thickness was investigated. The results indicated that at all frequency levels, silica aerogel/PET blankets enjoy higher SAC than their untreated counterparts. It was found that, SAC is strongly affected by the pore structure of aerogel particles. Silica aerogels with lower bulk densities, larger pore size and higher porosities exhibited better sound absorption performance. The results also indicated that hydrophobic aerogel blankets exhibit higher SAC as compared with hydrophilic blankets. The results also showed that the thickness of nonwoven fabric strongly affects the SAC of aerogel blankets.